Temperature Dependent Electrical Properties and Catalytic Activities of La2O3–CO2–H2O Phase System - Bahcine Bakiz; Frédéric Guinneton; Madjid Arab; Sylvie Villain; Abdeljalil Benlhachemi; Jean Raymond Gavarri (Advances in Materials Science and Engineering)
We present a study of electrical properties and catalytic activities of materials belonging to the hydrated carbonated system La2O3–CO2–H2O. The polycrystalline hydroxycarbonate, dioxycarbonate, and oxide are prepared via a coprecipitation route followed by heat treatment. The electrical conduction of the phases obtained by thermal decomposition from LaOHCO3, H2O is analyzed by electrical impedance spectroscopy, from 25°C to 950°C, under air. The catalytic properties of LaOHCO3, La2O2CO3 and La2O3 polycrystalline phases are studied by FTIR spectroscopy, in presence of gas mixtures CO-air and CH4-air, at temperatures ranging between 100°C to 525°C. The three materials behave differently in presence of CO or CH4 gases.